2009
DOI: 10.1021/pr900593r
|View full text |Cite
|
Sign up to set email alerts
|

An Altered Pattern of Liver Apolipoprotein A-I Isoforms Is Implicated in Male Chronic Hepatitis B Progression

Abstract: Chronic hepatitis B (CHB) appears to progress more rapidly in males than in females, and CHB-related hepatic cirrhosis and hepatocellular carcinoma are predominately diseases that tend to occur in men and postmenopausal women. To obtain more insight into the underlying mechanisms of gender disparity of CHB progress, two-dimensional difference gel electrophoresis was employed to compare liver proteome of C57BL/6 and HBV transgenic (HBV-Tg) mice both in male and female groups. We identified 8 differently express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 46 publications
3
32
0
2
Order By: Relevance
“…Males are more prone to contracting HCC caused by HBV than females. 51,52 This study showed a predominance of males as HBVcarriers and an elevated risk of CHB. As in previous reports, the host cell of males appears to be more susceptible to HBV in contracting chronic hepatitis and primary hepatocellular carcinoma than that of females.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Males are more prone to contracting HCC caused by HBV than females. 51,52 This study showed a predominance of males as HBVcarriers and an elevated risk of CHB. As in previous reports, the host cell of males appears to be more susceptible to HBV in contracting chronic hepatitis and primary hepatocellular carcinoma than that of females.…”
Section: Discussionmentioning
confidence: 69%
“…Scientists have recently determined that the basic Apo A-I isoform in males might be a key molecule associated with gender difference the progression of CHB. 51 The major limitation of this study was the retrospective design. This study did not exclude the possibility of bias and did not examine other confounding factors associated between HAL and non-alcoholic steatohepatitis, such as obesity, diabetes mellitus, hypertension, dyslipidemia, or metabolic syndrome.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…All over the world, including Nigeria, most studies have reported a greater tendency for HBV progression in males than females. [4][5][6][7][8][9][10][11][12][13][14] The higher seroprevalence in females demonstrated in this study may be explained by the circumcision history of most of the HBsAg positive females. Even though only 34.4% of the females had a history of circumcision, 16 of them (24.6%) were HBsAg seropositive.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was also verified in chronic hepatitis B patient serum. 14 In this seroprevalence study, the authors seized the opportunity of 2010 World Hepatitis Day to mount a public enlightenment campaign and screening of civil servants of Enugu State of Nigeria, for HBV infection using the surrogate marker, hepatitis B surface antigen (HBsAg). Selected risk factors for HBV transmission were also determined.…”
Section: Introductionmentioning
confidence: 99%